The Effect of Oil-Rich Food Waste Substrates, Used as an Alternative Carbon Source, on the Cultivation of Microalgae-A Pilot Study - Sniegoňová, Pavlína; Szotkowski, Martin; Holub, Jiří; Sikorová, Pavlína; Márová, Ivana (Microorganisms, 2023)
Microalgae are mostly phototrophic microorganisms present worldwide, showcasing great adaptability to their environment. They are known for producing essential metabolites such as carotenoids, chlorophylls, sterols, lipids, and many more. This study discusses the possibility of the mixotrophic abilities of microalgae in the presence of food waste oils. The utilization of food waste materials is becoming more popular as a research subject as its production grows every year, increasing the environmental burden. In this work, waste frying oil and coffee oil were tested for the first time as a nutrition source for microalgae cultivation. Waste frying oil is produced in large amounts all over the world and its simple purification is one of its greatest advantages as it only needs to be filtered from leftover food pieces. Coffee oil is extracted from waste spent coffee grounds as a by-product. The waste frying oil and coffee oil were added to the basic algal media as an alternative source of carbon. As a pilot study for further experimentation, the effect of oil in the medium, algal adaptability, and capability to survive were tested within these experiments. The growth and production characteristics of four algae and cyanobacteria strains were tested, of which the strain Desmodesmus armatus achieved exceptional results of chlorophyll (8.171 ± 0.475 mg/g) and ubiquinone (5.708 ± 0.138 mg/g) production. The strain Chlamydomonas reindhartii showed exceptional lipid accumulation in the range of 30-46% in most of the samples.
Keywords: microalgae; lipids; metabolites; coffee oil; waste frying oil; cyanobacteria